First report in Cuba of the presence of the louse Goniodes colchici (Denny, 1842) (Phthiraptera: Goniodidae) on Gallus gallus domesticus (Galliforme, Phasianidae). - Daisy Rodríguez García; Yenisey García Ferrer; Odalys Correoso Mendoza; Karel Bartelemy Carmenate; Maylin González Navarrete; Lissette Guzmán Gamboa (Acta Scientiarum. Animal Sciences, 2025)
Laying hens are affected by numerous species of lice. High infestations cause intense itching, irritation and destruction of feathers. In addition to interfering with the nutrition and rest of the birds, with the consequent impact on meat and egg production. Although several studies have been carried out on this topic in Cuba, findings of a species of louse were recently observed whose taxonomic characteristics differ from the species described in the country. The objective of the study is to report this new species of malophagous insect in Gallus gallus domesticus. Laying hens of the White Leghorn breed, 445 days old, from the Mayabeque province, Cuba, were sampled. From each bird, 3 to 5 feathers were extracted from seven regions of the body: head, back, wings, cloaca area, anterior thigh, tail and pectoral area. The collected specimens were mounted in Canada Balsam, on slides and coverslips for taxonomic identification under an optical microscope. The slides were placed in an incubator at 28ºC for seven days for clarification and subsequent identification. The level of infestation or intensity of invasion was determined taking into account the number of feather insects found. The taxonomic characteristics found in these insects coincide with those described for the species Goniodes colchici (Denny, 1842). The presence of the louse G. colchici (Phthiraptera: Goniodidae) on Gallus gallus domesticus is reported for the first time in Cuba.